A study on the range & deflection distance observation based on latitude position of artillery gun system - I Kang, Hwan; In Kim, Gun; Soo Kim, Hyun (International Journal of Engineering and Technology, 2018)
Background/Objectives: In this paper, instead of using the six degree of freedom trajectory for a projectile, we consider itsfour degree of freedom trajectory which is the NATO standard trajectory model. We consider the range and deflection distance observation based on latitude position of Artillery Gun System due to Coriolis acceleration.Methods/Statistical analysis: We obtain the trajectory of a projectile with 155 mm diameter using the Runge-Kutta method. We obtain the range and deflection distances associated with fire elevation angle when the launch position is located at differentposition of the artillery gun system. Its position is a function of the latitude.Findings: By changing the latitude of gun position, variation of range and the deflection distances are measured due to Coriolis force. Under the condition that the fire elevation is fixed, the range and deflection distances are calculated by numerical analysis. The maximum of the range is achieved at the equator. The minimum of deflection distance is observed near the Antarctic while the maximum valueof the deflection is observed at the North Pole.Improvements/Applications: This approach will be a good resource for analysis of delivery accuracy of the artillery gun system based on its position which is a function of latitude.Â